THE EFFECT OF THE LENGTH AND HEIGHT OF AN INCLINED PLANE AS A SIMPLE MACHINE ON THE TRAVEL TIME OF AN OBJECT - Nuriah Nuriah; Rama Yani (JURNAL ILMIAH NUSANTARA, 2025)
This practicum aims to introduce and understand how inclined planes work as a type of simple machine that can make it easier for humans to move objects. In this activity, students conduct experiments by launching candles onto various inclined planes of varying lengths, but at the same height of 5 cm. The lengths used were 10 cm, 15 cm, 20 cm, and 25 cm. Each plane was tested to determine the time it took the candle to travel from top to bottom. The results showed that the longer the inclined plane, the longer it took for the candle to reach the bottom. This suggests that a gentler inclined plane will slow the movement of an object but reduce the effort or energy required. This practicum not only helps students understand physics concepts directly through observation and experimentation but also makes them aware of the usefulness of simple tools like inclined planes in everyday life, such as a support board when lifting objects to higher places. Through this practicum, students are trained to think critically and carefully, and to connect theory to reality.